2021
DOI: 10.3390/ijms22020630
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuins as Important Factors in Pathological States and the Role of Their Molecular Activity Modulators

Abstract: Sirtuins (SIRTs), enzymes from the family of NAD+-dependent histone deacetylases, play an important role in the functioning of the body at the cellular level and participate in many biochemical processes. The multi-directionality of SIRTs encourages scientists to undertake research aimed at understanding the mechanisms of their action and the influence that SIRTs have on the organism. At the same time, new substances are constantly being sought that can modulate the action of SIRTs. Extensive research on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 216 publications
1
30
0
Order By: Relevance
“…Due to the increasing amount of scientific data on the participation of sirtuins in the pathomechanism and course of many diseases, there is a growing interest in the role of these enzymes in viral diseases, including HIV infection [19,30]. Due to their broad spectrum of activity and their regulation of many life processes or metabolic processes in the organism, their participation in viral infections is highly probable [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the increasing amount of scientific data on the participation of sirtuins in the pathomechanism and course of many diseases, there is a growing interest in the role of these enzymes in viral diseases, including HIV infection [19,30]. Due to their broad spectrum of activity and their regulation of many life processes or metabolic processes in the organism, their participation in viral infections is highly probable [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…They are also characterized by other enzymatic activities: ADP ribosylation (SIRT1, SIRT4 and SIRT6), desuccinylation and demalonylation (SIRT5), delipoylation (SIRT4), demyristoylation and depalmitoylation (SIRT6), and they have different cell localization: nuclear (SIRT1, SIRT6, SIRT7), cytoplasmic (SIRT2), and mitochondrial (SIRT3, SIRT4, SIRT5). So far, in terms of the development and course of many diseases, the best known are SIRT1, SIRT3, and SIRT6 [19]. Numerous studies on the use of activators or inhibitors of sirtuin activity in the treatment of neoplastic or metabolic diseases, mainly type 2 diabetes (T2DM), are currently being conducted [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Equally importantly, though this is yet to be fully understood, in addition to their deacetylase activity, these proteins can have alternative enzymatic activities, including ADP ribosylation (SIRT1, SIRT4 and SIRT6), desuccinylation and demalonylation (SIRT5), delipoylation (SIRT4) and depalmitoylation and demyristoylation (SIRT6). This breadth of functions is partly derived from sirtuin's diverse intracellular localizations: nuclear (SIRT1, SIRT6 and SIRT7), cytoplasmic (SIRT2), mitochondrial (SIRT3, SIRT4, SIRT5) [6][7][8][9]. The enzymes of the sirtuin family have similar chemical structure in both prokaryotes and eukaryotes.…”
Section: Sirtuins Family-the General Role In Organismsmentioning
confidence: 99%
“…Detailed information about their localization, function, role and main molecular targets are well described in many scientific publications [6][7][8][9], so therefore, we will not describe this data in detail in this study, but we will only present the most important information in terms of potential grab points for the action of sirtuins, which are common in the pathomechanism of HIV infection and the development of accompanying diseases.…”
Section: Sirtuins Family-the General Role In Organismsmentioning
confidence: 99%
“…Recent research has shown that SIRTs are activated in different organs and tissues. In addition, SIRT proteins have different localizations according to classification, such as the nucleus (SIRT1, SIRT6, and SIRT7) [11,12], cytoplasm (SIRT2), and mitochondria (SIRT3-SIRT5) [16,17]. Due to the different localizations, SIRTs are exposed to different environments, resulting in various physiological and potential pathological changes.…”
Section: Overview Of Sirtsmentioning
confidence: 99%